2012
DOI: 10.1186/1752-153x-6-38
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils from Leptospermums of the Sunshine Coast and Northern Rivers Regions

Abstract: BackgroundAround the turn of this century, the oil yield and chemical composition of Australian Leptospermum species was analysed. Since that time, research has been focused on their use as phytomedicines. The oil yield and composition of essential oils from Australian Leptospermum species directly impacts their commercialisation for medicinal use.ResultsThe essential oils from Leptospermum (L.) juniperinum, L. laevigatum, L. liversidgei, L. polygalifolium, L. semibaccatum, L. speciosum, L. trinervium and L. w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…The yield of our sample of L. petersonii was higher than other species of genus Leptospermum. In fact, Windsor and Brooks (2012) in their study observed a yield of 0.01-0.06% for Leptospermum laevigatum, 0.06-0.2% Leptospermum speciosum, and 0.2-0.4% for Leptospermum trinervium. Van Vuuren et al 2014demonstrated that for L. petersonii annual EO yields ranged from 0.4% (in February) and 1.8% (in March).…”
Section: Essential Oils Yield and Chemical Compositionmentioning
confidence: 89%
“…The yield of our sample of L. petersonii was higher than other species of genus Leptospermum. In fact, Windsor and Brooks (2012) in their study observed a yield of 0.01-0.06% for Leptospermum laevigatum, 0.06-0.2% Leptospermum speciosum, and 0.2-0.4% for Leptospermum trinervium. Van Vuuren et al 2014demonstrated that for L. petersonii annual EO yields ranged from 0.4% (in February) and 1.8% (in March).…”
Section: Essential Oils Yield and Chemical Compositionmentioning
confidence: 89%
“…GC-MS results were interpreted against NIST library, mass spectra of chemical references, and the literature on norisoprenoids and other volatiles from honeys and nectars including Leptospermum sources. 2327,28 The quantitation of compounds was undertaken by the internal standard method using hexadecane C 16 (stock 8.89 μg/100 mL) in the GC-MS analyses. The peak areas were standardized to hexadecane areas to the mass (μg/g) of individual components in honey.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…GC-MS results were interpreted against NIST library, mass spectra of chemical references, and the literature on norisoprenoids and other volatiles from honeys and nectars including Leptospermum sources. , …”
Section: Methodsmentioning
confidence: 99%
“…The genus Leptospermum belongs to the Myrtaceae family and includes approximately 80 species that are widespread around the world, particularly in Australia [6]. To date, only a small fraction of medicinal species in this genus have been analyzed chemically or explored for their potential biological activities [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%